Tie-Braces Design Optimization of Breasting Dolphin Structure at Petrochina Marine Terminal - Rudi Walujo Prastianto; Yoyok Setyo Hadiwidodo; Dyah Ayu Puspitorini (International Journal of Offshore and Coastal Engineering, 2017)
This paper discusses about optimization design of breasting dolphin’s structural strengthening with additional tie-braces. The breasting dolphin structure has failed because of the increased load on the export activity of tanker. A strengthening project has been carried out in 2014, but the result is considered overdesign and is not optimal. Therefore an optimization design of breasting dolphin structure is carried out as described herein, by looking for the optimum configuration, outside diameter, and wall thickness. The objective function is to determine the minimum weight of the structure. The independent variables are the outside diameter and wall thickness. The constraints are joint deflection check, member stress check, and joint punching shear stress check. There two type analyses performed. Firstly, in-place analysis of several structures with various tie-braces dimensions. The calculation of the initial tie-braces dimension was performed using parameter’s design according to API RP 2A WSD. Secondly is optimization analysis of output data from the in-place evaluation to determine optimum outside diameter and wall thickness of tie-braces, also the weight of the structure. After optimization analysis conducted it is found optimum structural weight be 261 tons, which is some 3 tons lighter than the previous one of 264 tons.